THE IMPACT OF LAND, SEA, AND AIR TRANSPORTATION INFRASTRUCTURE ON ECONOMIC GROWTH IN G7 COUNTRIES - Aryo Dwi Febriyanto; Hadi Sasana; Jalu Aji Prakoso; Muhammad Chrisna Satriagasa (MESP–FEB UNS, 2024)
This research analyzes the influence of road length, rail length, containers traffic, air freight, GFCF, and labor force on economic growth. This study uses quantitative methods with G7 countries as research objects during 2010-2021. Panel data consisting of 84 observations was analyzed with the help of Eviews12 software. The statistical analysis used in this research is the Ordinary Least Square (OLS) method, with the Fixed Effect Model chosen as the best model for interpreting the research results. The findings show that the road length, container traffic, air freight, GFCF, and the labor force have a positive and significant influence. Meanwhile, only the rail length does not have a significant effect on economic growth. Based on the results of this research, the theoretical implication of this research is the development of transportation infrastructure, especially road length, containers, air freight, GFCF, and labor force can increase economic growth in a country. So countries must consider spending on developing transportation infrastructure. Meanwhile, practically, this research can be used as study material in considering infrastructure development because the negative impact caused by errors in infrastructure development can be a waste of budget.